2020
DOI: 10.1192/bjp.2020.158
|View full text |Cite
|
Sign up to set email alerts
|

Imagery rescripting and eye movement desensitisation and reprocessing as treatment for adults with post-traumatic stress disorder from childhood trauma: randomised clinical trial

Abstract: Background Investigation of treatments that effectively treat adults with post-traumatic stress disorder from childhood experiences (Ch-PTSD) and are well tolerated by patients is needed to improve outcomes for this population. Aims The purpose of this study was to compare the effectiveness of two trauma-focused treatments, imagery rescripting (ImRs) and eye movement desensitisation and reprocessing (EMDR), for treating Ch-PTSD. Method We conducted an international, mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
77
3
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 68 publications
(90 citation statements)
references
References 32 publications
6
77
3
4
Order By: Relevance
“…The Beck depression inventory (Beck et al, 1961) score did not differ between groups (SE: M = 30.6, SD = 11.3; RE: M = 30.9, SD = 10.9). All participants were screened for psychiatric disorders using the structured clinical interview or mini international neuropsychiatric interview, as well as trauma history (see Boterhoven de Haan et al, 2020 for details and exclusion criteria).…”
Section: Studymentioning
confidence: 99%
See 3 more Smart Citations
“…The Beck depression inventory (Beck et al, 1961) score did not differ between groups (SE: M = 30.6, SD = 11.3; RE: M = 30.9, SD = 10.9). All participants were screened for psychiatric disorders using the structured clinical interview or mini international neuropsychiatric interview, as well as trauma history (see Boterhoven de Haan et al, 2020 for details and exclusion criteria).…”
Section: Studymentioning
confidence: 99%
“…We focus exclusively on differences in consistency between SE and RE, because the small case numbers do not permit an analysis of interaction effects with treatment type. The treatments and outcomes are reported elsewhere (see Boterhoven de Haan et al, 2020).…”
Section: Studymentioning
confidence: 99%
See 2 more Smart Citations
“…In a meta-analysis, Morina et al (16) conclude that ImRs holds promise as an effective and efficient intervention reducing psychological complaints associated with aversive memories. Furthermore, a recent study comparing ImRs and eye movement desensitization and reprocessing, a well-established evidencebased treatment for PTSD, showed that the two approaches were equally safe and effective in a population of patients with PTSD from childhood trauma (17).…”
Section: Introductionmentioning
confidence: 99%